Learning Speaking with Educational Influencers Content: A Case Study at Universitas Muhammadiyah Luwuk - Lakuana, Nurhaida; Eriyanti, Ribut Wahyu; Asih, Ria Arista; Widodo, Joko; Masduki (International Journal of English Language and Pedagogy, 2025)
This research aims to explore the use of digital learning platforms from educational influencers in improving English speaking skills among students in Indonesia. Qualitative methods with a case study design were used to collect data from seven students of second-semester of the English language education study program at University Muhammadiyah Luwuk. Sampling was carried out using purposive sampling, while the data collection instrument was a semi-structured interview. Data were analyzed using thematic analysis, which involves the steps of understanding the data, creating initial coding, finding themes, examining themes, mapping and naming themes, and preparing reports. The research findings highlight that platforms such as YouTube and TikTok are effective learning resources for students, by providing access to quality and structured learning content. Internal encouragement, students' willingness to learn, self-confidence, and flexible learning time are important in improving English speaking skills. This research contributes a deeper understanding of the role of digital technology in the context of English language learning in Indonesia and offers guidance for the development of more effective and relevant learning strategies.